2011
DOI: 10.1007/s11886-011-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Aggressive Glycemic Control Benefit Macrovascular and Microvascular Disease in Type 2 Diabetes?: Insights from ACCORD, ADVANCE, and VADT

Abstract: Diabetes is increasing rapidly worldwide and frequently results in severe vascular complications. A target glycated hemoglobin of less than 7% has commonly been recommended in hopes of preventing both macrovascular and microvascular complications. Although results from trials of intensive glycemic control have generally supported the notion that lower glycated hemoglobin values reduce microvascular disease, the evidence for similar benefits for macrovascular disease has been less clear. As macrovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 31 publications
2
50
0
2
Order By: Relevance
“…Several potential biological mechanisms might explain the association between DM and SCD. First, while a multifactorial control of DMassociated CVD risk factors (particularly blood pressure and dyslipidemia) can significantly reduce CVD risk in DM, recent trials have cast doubt on a beneficial effect of tight glucose control for the prevention of CVD [5], stimulating the research of the other mechanism(s) that may dilute the benefit of intensive glucose control. An increased risk of hypoglycaemic episodes has been suggested as a potential mechanism to explain this apparent lack of efficacy, as hypoglycaemic events are more frequent in intensive-treated diabetic subjects and they have long been associated with arrhythmic abnormalities [5].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
See 1 more Smart Citation
“…Several potential biological mechanisms might explain the association between DM and SCD. First, while a multifactorial control of DMassociated CVD risk factors (particularly blood pressure and dyslipidemia) can significantly reduce CVD risk in DM, recent trials have cast doubt on a beneficial effect of tight glucose control for the prevention of CVD [5], stimulating the research of the other mechanism(s) that may dilute the benefit of intensive glucose control. An increased risk of hypoglycaemic episodes has been suggested as a potential mechanism to explain this apparent lack of efficacy, as hypoglycaemic events are more frequent in intensive-treated diabetic subjects and they have long been associated with arrhythmic abnormalities [5].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…First, while a multifactorial control of DMassociated CVD risk factors (particularly blood pressure and dyslipidemia) can significantly reduce CVD risk in DM, recent trials have cast doubt on a beneficial effect of tight glucose control for the prevention of CVD [5], stimulating the research of the other mechanism(s) that may dilute the benefit of intensive glucose control. An increased risk of hypoglycaemic episodes has been suggested as a potential mechanism to explain this apparent lack of efficacy, as hypoglycaemic events are more frequent in intensive-treated diabetic subjects and they have long been associated with arrhythmic abnormalities [5]. A meta-analysis of about a million diabetic subjects has indeed evidenced a strong association between severe hypoglycaemic episodes and CVD risk [6] and, more recently, a specific increase of SCD events has been reported in intensively treated type 2 DM subjects [7].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…10 However, specific targets for hemoglobin A 1c (HbA 1c ) remain unclear, 10 and recent data challenge whether lower glycated hemoglobin values clinically benefit macrovascular disease. 24,25 For example, results from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial showed no significant reduction in macrovascular complications in patients with type 2 diabetes who had received intensive therapy (targeted HbA 1c level <6%) compared with standard therapy (targeted HbA 1c level 7%-7.9%). 25 In addition, patients receiving intensive therapy had increased mortality and a higher rate of hypoglycemia than patients receiving standard therapy.…”
Section: Optimal Medical Therapy Goals and Treatment Considerations Fmentioning
confidence: 99%
“…25 The decision to initiate intensive glucose management in an individual patient should therefore factor in the duration of diabetes, the presence of preexisting macrovascular disease or significant comorbidities, and hypoglycemic unawareness. 24 …”
Section: Optimal Medical Therapy Goals and Treatment Considerations Fmentioning
confidence: 99%
“…Microvascular and macrovascular complications are the major causes of morbidity and mortality in diabetic populations [2][3][4]. While intensive glucose control in patients with diabetes has been found to reduce the risk of microvascular complications, such as diabetic retinopathy [5], the beneficial effects of intensive glucose control on macrovascular and cardiovascular endpoints in type 2 diabetes are less clear [6,7].…”
Section: Introductionmentioning
confidence: 99%